The acute effects of combined isometric and plyometric conditioning activities on sprint acceleration and jump performance in elite junior sprinters - Pietraszewski, P.; Golas, A.; Zajac, A.; Mackala, K.; Krzysztofik, M. (Applied Sciences, 2025)
This study investigates the acute effects of a combined isometric and plyometric unilateral conditioning activity (CA) on post-activation performance enhancement (PAPE) in junior elite sprinters. The rationale for combining isometric and plyometric exercises lies in their complementary effects: isometric exercises enhance neuromuscular activation, while plyometric exercises may exploit the stretch-shortening cycle to maximize power output. Thirteen sprinters (10 males, three females) performed countermovement jumps (CMJ) and 50 m sprints before and after the CA protocol, which involved Bulgarian split squats (15% body mass) and single-leg hops. Performance metrics, including sprint times, CMJ height, and modified reactive strength index (RSImod), were recorded and analyzed. Results showed a significant improvement in CMJ height (2.6 ± 3.1%, p < 0.001) and RSI (4.1 ± 7.5%, p = 0.038), alongside a reduction in 20 m sprint time (-0.8 ± 1.4%, p = 0.012). No significant changes were observed in 40 m and 50 m sprint times or ground contact and flight times. These findings suggest that the applied CA selectively enhances sprint acceleration and vertical jumping performance, with a minimal impact on sprint distances above 20 m. This study underscores the potential of incorporating combined isometric and plyometric CAs into sprint training to optimize short-distance performance, though further research is needed to refine exercise protocols and explore long-term effects